2010
DOI: 10.1007/s12665-010-0621-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemistry, environmental isotopes and the origin of the Hamamayagi-Ladik thermal spring (Samsun, Turkey)

Abstract: Hamamayagi thermal spring (HTS) is located along the North Anatolian Fault Zone. The thermal spring has a temperature of 36°C, with total dissolved solids ranging from 485.6 to 508.5 mg/L. Hard, brittle, and gray limestones Permian aged are the reservoir rocks of the HTS. d 18 O-d 2 H isotope ratios clearly indicate a meteoric origin for the waters. The d 34 S value of sulfate in the thermal water is nearly 4.1% and implies a diagenetic environment characterized by reduced sulfur compounds. The d 13 C ratio fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Consequently, the shallow circulation of groundwater probably results in a short residence time, whereas long residence times may be related to deep groundwater circulation [34]. Thus, we can infer that the Group I samples occur in the shallow cold aquifer related to the local groundwater system, whereas the thermal springs of Group II rising from the deep groundwater system are recharged by deeply circulating meteoric water and are heated by the geothermal reservoir.…”
Section: Source Of Rechargementioning
confidence: 95%
“…Consequently, the shallow circulation of groundwater probably results in a short residence time, whereas long residence times may be related to deep groundwater circulation [34]. Thus, we can infer that the Group I samples occur in the shallow cold aquifer related to the local groundwater system, whereas the thermal springs of Group II rising from the deep groundwater system are recharged by deeply circulating meteoric water and are heated by the geothermal reservoir.…”
Section: Source Of Rechargementioning
confidence: 95%
“…5), which δ 34 S values resembling to arc volcanic magmas typically in a range between 0 and 10‰ (Ueda and Sakai 1984). On the other hand, elevated HCO3in High-HCO3fluid may be originated of CO2 gas released from some heat sources that was dissolved in waters and preferentially transported towards surface leaving SO2 and other gasses (e.g., Ohsawa et al 2002;Gultekin et al 2011). The use of δ 13 C tracer in dissolved inorganic carbon can provide clue to test this hypothesis (Chiodini et al 2000;Yamada et al 2011;Rive et al 2013).…”
Section: Deep Fluid Upwellingmentioning
confidence: 99%
“…Since the fossils in the study were found incidentally from the coal mines in that region, there is little information about the exact locality and stratigraphic level. Although there are various studies on the geology of the region (such as Öztürk, 1979;Aktimur et al, 1992;Gültekin et al, 2011), there is not enough study on the Quaternary.…”
Section: Localitymentioning
confidence: 99%